ENFORCEMENT OF SOCIAL MEDIA PROMOTIONAL SERVICES AGREEMENTS ACCORDING TO INDONESIAN POSITIVE LAW - Salsabilah Anton; Mas Anienda Tien (Universitas Islam Balitar, 2022)
This study aims to determine the validity of the promotional service agreement and to find out the legal remedies for losses on defaults carried out by the influencer in the promotion agreement on social media. This study is a normative legal study type. The data sources in this study used primary legal material, secondary legal materials, and also tertiary legal materials. The results of the study can be concluded that the promotion service agreement (endorsement) is included in an oral agreement formed through social media, and is an anonymous agreement, because the agreement is not regulated in the legislation. The promotional service agreement is valid in accordance with the legal terms of the agreement in the book of civil law article 1320 and is binding both parties. In the agreement, there has been a default by the influencer to the online shop. The form of default that occurs is influencer do not carry out their obligations in promoting a product according to the initial agreement and it is not uncommon for influencer to be late in promoting a product on their social media. Default in the promotional service agreement can ensure that the parties apply good principles in carrying out the agreement, understand the rights and obligation of both parties, and can receive sanction in the agreement, so that both parties can be more responsible. If there has been a default in the promotional service agreement, the appropriate dispute resolution is through alternative dispute resolution in the form of negotiations that can be carried out by both parties. This study aims to determine the validity of the promotional service agreement and to find out the legal remedies for losses on defaults carried out by the influencer in the promotion agreement on social media. This study is a normative legal study type. The data sources in this study used primary legal material, secondary legal materials, and also tertiary legal materials. The results of the study can be concluded that the promotion service agreement (endorsement) is included in an oral agreement formed through social media, and is an anonymous agreement, because the agreement is not regulated in the legislation. The promotional service agreement is valid in accordance with the legal terms of the agreement in the book of civil law article 1320 and is binding both parties. In the agreement, there has been a default by the influencer to the online shop. The form of default that occurs is influencer do not carry out their obligations in promoting a product according to the initial agreement and it is not uncommon for influencer to be late in promoting a product on their social media. Default in the promotional service agreement can ensure that the parties apply good principles in carrying out the agreement, understand the rights and obligation of both parties, and can receive sanction in the agreement, so that both parties can be more responsible. If there has been a default in the promotional service agreement, the appropriate dispute resolution is through alternative dispute resolution in the form of negotiations that can be carried out by both parties.